Interpretation of El Niño–Southern Oscillation‐related precipitation anomalies in north‐western Borneo using isotopic tracers. Issue 14 (21st June 2018) - Kurita, Naoyuki; Horikawa, Mayumi; Kanamori, Hironari; Fujinami, Hatsuki; Kumagai, Tomo'omi; Kume, Tomonori; Yasunari, Tetsuzo
Abstract: We examined rainfall anomalies associated with the El Niño–Southern Oscillation (ENSO) in northern Sarawak, Malaysia, using the oxygen isotopic composition of rainfall. Two precipitation‐sampling campaigns were conducted for isotope analysis: (a) at the Lambir Hill National Park (4.2° N, 114.0° E) from July 2004 to October 2006 and (b) at the Gunung Mulu National Park (3.9° N, 114.8° E) from January 2006 to July 2008. The records from these campaigns were merged with a previously published rainfall isotope dataset from Gunung Mulu site to create a 7‐year‐long record of the oxygen isotopic composition of Sarawak rainfall. The record exhibits clear intraseasonal variations (ISVs) with periods ranging from 10 to 70 days. The ISVs of 10‐ to 90‐day band‐pass filtered oxygen isotopic composition are linked to the synoptic‐scale precipitation anomalies over the southern South China Sea (SCS). The lead–lag correlation map of precipitation with the filtered oxygen isotope anomalies shows that an anomalous wet condition responsible for the decrease in oxygen isotopic composition appears over the SCS in association with the passage of north‐eastward propagation of the boreal summer intraseasonal oscillation (BSISO) in the summer monsoon season. The anomalous wet condition in spring is connected with eastward‐propagating Madden–Julian oscillation (MJO), whereas the sustained wet condition in winter is responsible for the occurrence of the Borneo vortex (BV) over the SCS. ENSO modulates the frequency of these synoptic conditions on a seasonal and longer time scale, showing a strong correlation between the seasonal isotopic anomalies and the Southern Oscillation index. We therefore discern, from the significant correlation between the isotope anomalies and area‐averaged Sarawak rainfall anomalies ( R  = −0.65, p  < 0.01), that ENSO‐related precipitation anomalies are linked to the seasonal modulation of the BSISO and MJO activity and BV genesis.